Granulocyte colony-stimulating factor in secondary prophylaxis for advanced-stage Hodgkin lymphoma treated with ABVD chemotherapy: a cost-effectiveness analysis. Issue 8 (2nd August 2016) - Cheung, M. C.; Prica, A.; Graczyk, J.; Buckstein, R.; Chan, K. K. W.
Abstract: Granulocyte colony-stimulating factor (G-CSF) is commonly administered to patients with Hodgkin lymphoma (HL) with neutropenia. We constructed a decision-analytic model to compare the cost-effectiveness of secondary prophylaxis with G-CSF to a strategy of 'no G-CSF' in response to severe neutropenia for adults with advanced-stage HL treated with ABVD. A Canadian public health payer's perspective was considered and costs were presented in 2013 Canadian dollars. The quality-adjusted life years (QALYs) attained with the G-CSF and 'no G-CSF' strategies were 1.403 and 1.416, respectively. Costs for the strategies with and without G-CSF were $38, 971 and $33, 982, respectively. In the base case analysis, the 'no G-CSF' strategy was associated with cost savings and improved QALYs; therefore, 'no G-CSF' was the dominant approach. For patients with severe neutropenia during ABVD chemotherapy for advanced-stage HL, a strategy without G-CSF support is associated with improved quality-adjusted outcomes, cost savings, and is the preferred approach.